ASSESSMENT OF RILMENIDINE EFFICIENCY IN PATIENTS WITH ARTERIAL HYPERTENSION WITH DETERIORATION OF DAILY PROFILE OF BLOOD PRESSURE - P. P. Tikhonov; L. A. Sokolova (Столичная издательская компания, 2015)
Aim. To estimate an efficiency and tolerability of rilmenidine in hypertensive patients with different types of blood pressure (BP) daily profile - dipper and non-dipper. Methods. 23 patients with essential hypertension (EH), I-II stages, were included into the study. They were treated with rilmeneidine 1 mg daily during one month. Ambulatory BP monitoring (ABPM) and office BP measurements were made before and after the treatment. Based on ABPM results all patients were divided into two groups: with adequate decrease of BP at nighttime (dipper, D), and with insufficient decrease of BP at nighttime (non-dipper, ND). Results. One month rilmenidine monotherapy resulted in BP normalization in 52% of patients. Decrease in 24-hour BP, daytime and nighttime BP, burden with BP and BP variability during daytime was observed in both groups. A distinction in rilmenidine influence on BP daily index was revealed: initially normal BP daily index didn't change in D group, while initially decreased BP daily index increased in ND group. Rilmenidine reduced the speed of morning BP rise in patients of ND group. Conclusion. Results of the study testify efficiency and satisfactory tolerability of monotherapy with rilmenidine 1 mg daily in patients with EH of I-II stages. For patients with insufficient decrease in BP during nighttime rilmenidine provides normalization of BP daily profile intensifying BP night decrease and reducing the speed of morning BP rise.